International project: Media coverage of the Polish EU presidency - Stępińska, Agnieszka (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
Effectively conducted, the EU presidency can improve the image of the country holding this position. This is particularly true for countries that are holding the chairmanship of the EU Council for the first time. During the six-month period of the presidency the country attracts foreign media attention, not only as a host of numerous meetings and events, but also as an actor in charge of defining the major directions of the EU policy. Therefore, that time could be spent on achieving political goals and build- ing an image as an important and effective EU member, as well as an at- tractive country for tourists and entrepreneurs. In many cases, however, internal political events such as elections, political tensions, or controver- sies over domestic issues seem to take over the atmosphere around the country.